Effective remediation of fish processing waste using mixed culture biofilms capable of simultaneous nitrification and denitrification. (23rd May 2016) - Markande, Anoop R.; Kapagunta, Chandrika; Patil, Pooja S.; Nayak, Binaya B.
Abstract : Fish processing waste water causes pollution and eutrophication of water bodies when released untreated. Use of bacteria capable of simultaneous nitrification and denitrification (SND) as biofilms on carriers in a moving bed bioreactor (MBBR) is a popular approach but seldom used for fish processing waste water remediation. Here, we studied the variations in biofilm formation and application activities by isolates Lysinibacillus sp. HT13, Alcaligenes sp. HT15 and Proteus sp. HT37 previously reported by us. While HT13 and HT15 formed significantly higher biofilms in polystyrene microtitre plates than on carriers, HT37 exhibited highest on carriers. A consortium of the three selected bacteria grown as biofilm on MBBR carriers exhibited better remediation of ammonia (200–600 ppm and 50 mM) than the individual isolates on carriers. The mixed biofilm set on the carriers was used for nitrogenous waste removal from fish processing waste water in 2 and 20 L setups. The total nitrogen estimated by elemental analysis showed complete remediation from 250 ppm in both 2 and 20 L waste water systems within 48 h. The usual toxic nitrogenous components—ammonia, nitrite and nitrate were also remediated efficiently.